Author Correction: Single-cell RNA-seq reveals that glioblastoma recapitulates a normal neurodevelopmental hierarchy - Couturier, Charles P.; Ayyadhury, Shamini; Le, Phuong U.; Nadaf, Javad; Monlong, Jean; Riva, Gabriele; Allache, Redouane; Baig, Salma; Yan, Xiaohua; Bourgey, Mathieu; Lee, Changseok; Wang, Yu Chang David; et al. (Nature communications, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.An amendment to this paper has been published and can be accessed via a link at the top of the paper.